KARDIOCHIRURGIA DOROSŁYCHIntraoperative assessment of grafts in coronary revascularization using the transit-time flowmetry method (TTF) - Żelazny, Piotr; Szapiel, Grzegorz; Witt-Majchrzak, Anna; Buzun, Leszek; Dmyterko, Andrzej; Kukliński, Maciej; Morozow, Lew (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2010)
Background: Transit-time flowmetry is a relatively new method and enables intraoperative assessment of flow parameters in coronary artery bypass grafts. Aim: We studied the use of transit-time flow measurements to determine the ability of the method to detect technical errors in grafting and its influence on early outcomes. Material and methods: From October 17, 2006, to July 30, 2009, we carried out a prospective randomized study relating to patients undergoing isolated CABG in our institution. All patients were stratified into two groups: group A consisted of 305 pts in whom we performed TTF measurements and group B of 583 pts without TTFM. Almost all cases in both groups underwent off-pump CABG and total arterial revascularization in Y and T configuration (group A 99.3%; 91.8% vs. group B 98.6%; 86.9% respectively). Graft patency was assessed using flow curves, mean flow (Qm), pulsatility index (PI) and diastolic filling percentage (DF). Results: In group A, 29 anastomoses in 28 (9.2%) patients flow measurement showed unacceptable results of checked parameters. After the revision of the anastomoses in these 28 pts measurements obtained were acceptable and differences were statistically significant (Qm p < 0.0001; PI p < 0.001; DF p 0.05; perioperative MI p > 0.05; IABP support p > 0.05; haemofiltration p > 0.05). Conclusions: Transit-time flow measurement enables functional problems to be diagnosed, allowing intraoperative verification and correction of the grafts. However, comparing these two large groups, with or without TTFM, the majority of postoperative early complications did not reach statistical significance, if the p value was set at p ≤ 0.05.